(untitled) (Вісник: Міжнародні відносини, 2024)
The article analyzes the problems of innovation-driven development in the conditions of the information society. Innovations appear as a most powerful factor in economic growth and sustainable international competitiveness of nations in the global environment. Under the conditions of global competition, the factors fostering innovative growth become important, mobilizing internal resources of a country – financial, human, intellectual and creative capital, and supporting its business. External economic factors are also important, namely the development of international scientific and technical cooperation, international alliances, the involvement of multinational corporations, inclusion in global value chains, etc. One of the most important factors is the development of human and intellectual capital, since a human being personifies intellect, experience, knowledge, ideas, values, and management skills, and these factors enable many countries to use these advantages when implementing an innovation-driven development strategy. These problems are especially relevant for Ukraine, since it is the innovation-driven development model that will be the basis of the post-war reconstruction of the country, which will allow the economy to be restored at a new technological level and ensure resilient economic growth, competitive positions on the world market, and the well-being of the population.